2022
DOI: 10.1371/journal.ppat.1010251
|View full text |Cite
|
Sign up to set email alerts
|

Live imaging of Yersinia translocon formation and immune recognition in host cells

Abstract: Yersinia enterocolitica employs a type three secretion system (T3SS) to translocate immunosuppressive effector proteins into host cells. To this end, the T3SS assembles a translocon/pore complex composed of the translocator proteins YopB and YopD in host cell membranes serving as an entry port for the effectors. The translocon is formed in a Yersinia-containing pre-phagosomal compartment that is connected to the extracellular space. As the phagosome matures, the translocon and the membrane damage it causes are… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…To minimize the label error for MINFLUX nanoscopy, an ALFA‐tag was introduced into YopD's extracellular domain (giving rise to YopD‐ALFA). It was demonstrated that the ALFA‐tag did not compromise the central functions of YopD during protein translocation by the Y. enterocolitica T3SS (Rudolph et al., 2022). MINFLUX nanoscopy allowed to visualize single YopD‐ALFA molecules bound by fluorescent nanobodies in Yersinia translocation pores.…”
Section: Fluorescence Srm In Secretion Systemsmentioning
confidence: 99%
“…To minimize the label error for MINFLUX nanoscopy, an ALFA‐tag was introduced into YopD's extracellular domain (giving rise to YopD‐ALFA). It was demonstrated that the ALFA‐tag did not compromise the central functions of YopD during protein translocation by the Y. enterocolitica T3SS (Rudolph et al., 2022). MINFLUX nanoscopy allowed to visualize single YopD‐ALFA molecules bound by fluorescent nanobodies in Yersinia translocation pores.…”
Section: Fluorescence Srm In Secretion Systemsmentioning
confidence: 99%
“…WA-314 YopD-ALFA was generated using a CRISPR-Cas12a-assisted recombineering approach as described previously [50,51].…”
Section: Antibodies and Nanobodiesmentioning
confidence: 99%
“…This also offers the advantage of flexible approaches, for example, when the same molecule is to be studied using different nanoscopy techniques or imaging modalities (e.g., multicolor imaging or single molecule tracking). We have recently established in situ modification of injectisome proteins with a short peptide (ALFA) tag [43]. The ALFA tag can bind with high affinity to different fluorophore-labeled nanobodies (NbALFA) [42].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since its introduction in 2019, ALFA-tagging has been applied in various systems [ 3 , 4 , 5 ], but to the best of our knowledge not yet in nematodes. Nematodes represent one of the major animal phyla with an estimated species number of more than a million [ 6 ], with free-living, as well as animal and plant parasitic species [ 7 ].…”
Section: Introductionmentioning
confidence: 99%